2014
DOI: 10.1136/heartjnl-2014-306118.190
|View full text |Cite
|
Sign up to set email alerts
|

190 Nox2 Activation and Oxidative Damage of Cerebral Vasculature and Locomotor Function in Ageing Mice

Abstract: Oxidative stress and oxidative damage of cerebral vasculature and neuronal cells have been found to play an important role in ageing-related neurodegenerative behaviour disorders. Although several enzymatic sources are involved in brain ROS generation, recently NADPH oxidase 2 (Nox2) has been suggested as a major source of ROS generation in ageing-related vascular dysfunction and neurodegenerative diseases. In this study, we used age-matched littermates of wild-type (WT) and Nox2 knockout (Nox2-/-) mice on a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, mitochondria are not only targets for ROS but also significant sources of ROS, which under certain conditions may stimulate NAD(P)H oxidases [ 12 ]. In fact, many studies demonstrated the principal role of NAD(P)H oxidase activity in aged-mediated ROS generation in mouse models [ 21 - 23 ] and the improvement of endothelial function by the inhibition of NAD(P)H oxidase or scavenging of O2- [ 24 , 25 ]. In particular, it has been reported that NAD(P)H oxidase 4 is involved in O2- formation and cellular senescence in ageing, and its inhibition counteracted oxidative stress in pulmonary and kidney arteries of aged rats, as well as in lungs of aged mice [ 26 - 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mitochondria are not only targets for ROS but also significant sources of ROS, which under certain conditions may stimulate NAD(P)H oxidases [ 12 ]. In fact, many studies demonstrated the principal role of NAD(P)H oxidase activity in aged-mediated ROS generation in mouse models [ 21 - 23 ] and the improvement of endothelial function by the inhibition of NAD(P)H oxidase or scavenging of O2- [ 24 , 25 ]. In particular, it has been reported that NAD(P)H oxidase 4 is involved in O2- formation and cellular senescence in ageing, and its inhibition counteracted oxidative stress in pulmonary and kidney arteries of aged rats, as well as in lungs of aged mice [ 26 - 28 ].…”
Section: Introductionmentioning
confidence: 99%